Mediating effect of school climate and teachers’ empowerment on transformational leadership and school effectiveness at selected primary schools in Peninsular Malaysia - Maniam, Indra Devi (2022)
The purpose of this study is to explore the mediating effect of school climate, teachers’ empowerment on transformational leadership and school effectiveness at selected primary schools in Peninsular Malaysia based on teachers’ perception. This study also investigates the level of transformational leadership, school climate, teacher’ empowerment and school effectiveness based on school types. Additionally, this study also explores the relationship between transformational leadership, school climate, teachers’ empowerment, and school effectiveness. Based on literature review, transformational leadership, school climate and teachers’ empowerment were proposed as an ideal factor contributes to school effectiveness. Besides, number of studies on transformational leadership, school climate, teachers’ empowerment, and school effectiveness in Malaysian context is still limited and more investigation were required on these variables in schools to identify their contribution to school effectiveness. This study utilized stratified random sampling method by choosing 72 primary schools and 504 teachers with the response rate of 432 (n=432) in four states of Peninsular Malaysia (Pahang, Perak, Johor, and Selangor) and from three types of schools namely National, National type Chinese and National type Tamil schools. Data analysis was conducted by using descriptive statistic, Pearson Product-moment correlation analysis, Structural Equation Modelling (SEM) and PROCESS Macro for SPSS. Additionally, confirmatory factor analysis (CFA) was done to better fit the model. Moreover, reliability and validity analysis (content, construct, convergent and discriminant) were also done to confirm that the instrument is valid as well as reliable. The findings of descriptive analysis revealed that the level of transformational leadership, school climate, teachers’ empowerment and school effectiveness were at high level in three types of primary schools in Peninsular Malaysia based on teachers’ perception. The result of Pearson Product-moment correlation analysis indicated that, there is a positive, significant, and strong correlation between the transformational leadership and school effectiveness. The result showed a positive, significant, and strong relationship between transformational leadership and school climate. The findings revealed a positive, significant, and strong correlation between transformational leadership and teachers’ empowerment. The study also revealed a strong, positive correlation between school climate and school effectiveness. The findings also indicated a strong and positive correlation between teachers’ empowerment and school effectiveness. The result of SEM analysis showed that school climate does not mediate the relationship between transformational leadership and school effectiveness. The mediation analysis also showed that there is a positive and partial mediation effect of teachers’ empowerment on the relationship between transformational leadership and school effectiveness. Additionally, the mediation analysis was carried out using PROCESS macro analysis and result of the analysis indicated that transformational leadership could have significant direct effect through school climate and teachers’ empowerment on school effectiveness. Overall, the main findings illuminate the influence of transformational leadership practices on school effectiveness, directly and through school climate and teachers’ empowerment. Finally, this study proposed several recommendations to Ministry of Education, policy makers, headmaster and teachers, to improve the level of school effectiveness by practising transformational leadership practices, school climate and teachers’ empowerment as to fulfil the current changes and reformation in education system in Malaysia.